Ultrasound image-guided gene delivery using three-dimensional diagnostic ultrasound and lipid-based microbubbles. (7th February 2022) - Omata, Daiki; Munakata, Lisa; Kageyama, Saori; Suzuki, Yuno; Maruyama, Tamotsu; Shima, Tadamitsu; Chikaarashi, Takumi; Kajita, Naoya; Masuda, Kohji; Tsuchiya, Naoto; Maruyama, Kazuo; Suzuki, Ryo
Abstract: Gene therapy is a promising technology for genetic and intractable diseases. Drug delivery carriers or systems for genes and nucleic acids have been studied to improve transfection efficiency and achieve sufficient therapeutic effects. Ultrasound (US) and microbubbles have also been combined for use in gene delivery. To establish a clinically effective gene delivery system, exposing the target tissues to US is important. The three-dimensional (3D) diagnostic probe can three-dimensionally scan the tissue with mechanical regulation, and homogenous US exposure to the targeted tissue can be expected. However, the feasibility of therapeutically applying 3D probes has not been evaluated, especially gene delivery. In this study, we evaluated the characteristics of a 3D probe and lipid-based microbubbles (LB) for gene delivery and determined whether the 3D probe in the diagnostic US device could be used for efficient gene delivery to the targeted tissue using a mouse model. The 3D probe RSP6-16 with LB delivered plasmid DNA (pDNA) to the kidney after systemic injection with luciferase activity similar to that of probes used in previously studies. No toxicity was observed after treatment and, therefore, the combined 3D probe and LB would deliver genes to targeted tissue safely and efficiently.